Tinjauan Histologi Sawar Darah Otak - Yuliana, Ida (Pendidikan Dokter Universitas Lambung Mangkurat, 2013)
Abstract: Blood brain barrier is a membrane which is highly resistant to the diffusion process and separate the blood brain interstitial fluid. The blood brain barrier is a separation between the main compartment nervous system brain, CSF and the third compartment of the blood. Function of the blood brain barrier are protects the central nervous system to maintain homeostasis of blood milieu microenvironment. Blood-brain barrier layer is characterized as a perfect and continuous cell of endothelial cells in the connective by tight junctions. By using electron microscopy showed that the lumen of blood capillaries separated from the extra-cellular space by endothelial cells in the capillary wall (cell cerebral endhothelial), basement membrane outside the cell contains perisit endothelial cells and astrocytes feets are attached to the outer layer of the wall of the capillary. The third component has a specificity in terms of functional morphology and histology. Keywords: blood-brain barrier, endothelial cell, astrocyte, perisit cell Abstrak: Sawar darah otak adalah suatu membran yang sangat resisten terhadap proses difusi dan memisahkan cairan intersisial otak darah. Sawar darah otak merupakan pemisah antara kompartmen utama susunan saraf otak, LCS dan kompartmen ketiga yaitu darah. Sawar darah otak memiliki fungsi melindungi susunan saraf pusat dari milieu darah mempertahankan homeostasis lingkungan mikro. Sawar darah otak dicirikan sebagai lapisan seluler yang sempurna dan kontinu dari sel endotel yang di ikat oleh tight junction. Dengan menggunakan mikroskop elektron memperlihatkan bahwa lumen kapiler darah dipisahkan dari ruang ekstra seluler oleh sel endotelial di dinding kapiler (cell cerebral endhothelial), membran basalis di luar sel endotel berisi sel perisit dan kaki-kaki astrosit yang menempel pada lapisan luar dari dinding kapiler. Ketiga komponen tersebut memiliki kekhususan dalam hal morfologi dan fungsional secara histologi. Kata-kata Kunci: sawar darah otak, sel endotel, astrosit, sel perisit